Pandalisines A and B, novel indolizidine alkaloids from the leaves of Pandanus utilis. Issue 19 (1st October 2015) - Cheng, Yuan-Bin; Tsai, Yi-Hong; Lo, I-Wen; Haung, Chen-Chang; Tsai, Yu-Chi; Beerhues, Ludger; El-Shazly, Mohamed; Hou, Ming-Feng; Yuan, Shyng-Shiou; Wu, Chin-Chung; Chang, Fang-Rong; Wu, Yang-Chang
Graphical abstract: Abstract: Two novel alkaloids named pandalisines A (1 ) and B (2 ), constituting a new class of C8-substituted indolizidine moiety, were isolated from the leaves of Pandanus utilis . The structures of these new compounds were established by their mass and spectroscopic data. The absolute configuration was determined by the comparison of experimental CD and calculated ECD spectra. A plausible biosynthetic pathway for compounds1 and2 is advanced. The cytotoxic activities of the isolated alkaloids against A-549, Hep-G2, and MDA-MB-231 cancer cell lines were evaluated. The result showed that1 and2 are the first non-cytotoxic indolizidine alkaloids.